From Cowboy Detectives to Soldiers of Fortune: Private Security Contracting and Its Contradictions on the New Frontiers of Capitalist Expansion - Weiss, Robert P. (Social justice, 2007)
The writer examines the current resurgence, global expansion, and market consolidation of the private security industry. The modern boom in private security is partly driven by the revival of an old service for new markets: helping with original accumulation. Private security has once again been called upon to help clear a path for capitalist exploitation, assisting with primitive accumulation in a transnational neoliberal venture that operates mostly through “accumulation by dispossession.” In exchange, the neoliberal economic policies of global privatization and economic deregulation are creating the ideal conditions for the success of private security entrepreneurs who offer for sale a variety of services to governmental, nongovernmental, and transnational corporate customers.